Legal Protection of Inheritance Rights of Children from Unregistered Marriages (Analysis of Supreme Court Decision No. 671 K/Ag/2015) - Kathrin Makdalena BR Siregar, Widya; Listyawati, Peni Rinda; Hasana, Dahniarti (Jurnal Konstatering, 2025)
Abstract. A valid marriage in Indonesia requires its implementation in accordance with religious law and registration by an authorized official for legal certainty. Children born from unregistered marriages have only a civil relationship with the mother and her family. However, the inheritance rights of children from unregistered marriages have undergone progressive development through jurisprudence. This study aims to analyze the legal status of inheritance rights of children from unregistered marriages within the context of legal certainty and to examine the legal protections afforded to these children. This research method uses normative legal research. The approaches used are the statute approach and the conceptual approach. The data type is qualitative, and the data sources are secondary data. The data collection method is through literature review, while data analysis is conducted descriptively. The research findings indicate that although unregistered marriages are religiously valid, the lack of administrative registration traditionally limits children's rights. However, Constitutional Court Decision No. 46/PUU-VIII/2010 has recognized the civil relationship of children with their biological fathers based on scientific or other evidence. Supreme Court Decision No. 671 K/AG/2015 further affirmed the inheritance rights of children from unregistered marriages, prioritizing the principle of substantive justice in accordance with Gustav Radbruch's Theory of Legal Certainty. Legal protection for children, as stipulated in Law No. 35 of 2014 concerning Child Protection, applies without discrimination based on origin. Legal remedies for obtaining legitimate child status for children from unregistered marriages include Marriage Confirmation in the Religious Court for Muslims, and marriage registration in the District Court for non-Muslims, which then facilitates the issuance of complete birth certificates. Nevertheless, challenges in the implementation and access to comprehensive children's rights remain, demanding more holistic and proactive policy reforms.